Estrategias comunicacionales de las empresas para motivar a sus equipos de trabajos - Moran Lara, Ginger Nicol (2024)
The objective of the general research focused on Analyzing the incidence of the company's communication strategies in relation to performance and work motivation in the Esika company belonging to the Puebloviejo Canton, province of Los Ríos, the research is descriptive under a No design. experimental based on the inductive and deductive methods, the population and the sample were made up of 30 workers and the manager of the beauty company Esika, the following data collection techniques were applied according to each variable of the study, for which The survey was used and its instruments consisted of a questionnaire of multiple choice questions, which were established to be subjected to analysis and brought to a statistical report by creating graphs that visualize the results obtained. In this sense, the study carried out determined that the impact of communication strategies on the functionality of a company is notably linked to performance and work motivation since it was evident that this is an indispensable factor that provides a better environment and work environment. job.